Стратегические направления промышленной политики в металлургической отрасли Украины в посткризисный период - Никифорова, В.А. (Економіка промисловості, 2012)
Обоснована целесообразность разработки промышленной политики в современных условиях хозяйствования. Проанализирована ретроспектива государственной промышленной политики в металлургии Украины в кризисный и посткризисный периоды. Выделены главные проблемы развития украинской металлургической промышленности и определены базовые приоритеты, направления и меры украинской государственной промышленной политики в отрасли.
Ключевые слова: промышленная политика, металлургия, стратегические направления развития. Обґрунтовано доцільність розробки промислової політики в сучасних умовах господарювання. Проаналізовано ретроспективу державної промислової політики в металургії України у кризовий та посткризовий періоди. Виділено головні проблеми розвитку української металургійної промисловості та визначено базові пріоритети, напрями й заходи української державної промислової політики в галузі.
Ключові слова: промислова політика, металургія, стратегічні напрями розвитку. The expediency of developing the industrial policy in the contemporary economy is substantiated. It is revealed that the problems of the industrial policy in the developed and developing countries differ significantly as a result of uneven economic growth.
Retrospective of the state industrial policy in the metallurgy of Ukraine in the crisis and post crisis periods is analyzed. The main anticrisis government measures, their objectives and results of actions are defined. The measures turned out to be short-lived and did not solve the underlying structural and technological problems of the industry. Consequently, the dynamics of the major industrial and economic performance of the industry in the period under review was negative.
In the paper, the main problems of Ukraine's steel industry are identified, among which the most important problem is high energy intensity of production, its low technological level and assortment deformation of the structure of steel products production and consumption. The priorities, directions and measures of the Ukrainian state industrial policy in the above industry are marked with a shift of emphasis in favor of the realization of strategic objectives – improving the efficiency of resources and ecology.
Keywords: industrial policy, metallurgy, strategic directions for development.